(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2026)
Rodent-borne diseases remain a significant public health concern, particularly in communities with inadequate environmental sanitation and limited health literacy. In Ibu District, West Halmahera, low community awareness regarding disease transmission and prevention increases the risk of infection. This Community Partnership Program aimed to improve community knowledge and awareness of rodent-borne diseases and promote preventive behaviors through a participatory health education approach. The intervention was conducted through structured counseling sessions, interactive discussions, and educational materials focusing on transmission pathways, environmental sanitation, and household-level prevention strategies. The results showed a significant improvement in participants’ knowledge, with understanding increasing from 60% to 92% after the intervention. In addition, participants demonstrated greater awareness and engagement in maintaining environmental hygiene. In conclusion, participatory community-based health education effectively enhances knowledge and promotes positive behavioral change in preventing rodent-borne diseases.